Women and religion in medieval and Renaissance Italy - Bornstein, Daniel; Rusconi, Roberto; Schneider, Margery J. (Chicago (Ill.) University of Chicago press, 1996)
Between the twelfth and the sixteenth centuries, women assumed public roles of unprecedented prominence in Italian religious culture. Legally subordinated, politically excluded, socially limited, and ideologically disdained, women's active participation in religious life offered them access to power in all its forms. These essays explore the involvement of women in religious life throughout northern and central Italy and trace the evolution of communities of pious women as they tried to achieve their devotional goals despite the strictures of the ecclesiastical hierarchy. The contributors examine relations between holy women, their devout followers, and society at large. (publisher's description)
Keywords: Catholic Church -- Italy -- History; Christian women saints -- Italy -- History; Monasticism and religious orders for women -- Italy -- History -- Middle Ages, 600-1500; Spirituality -- Catholic Church&delete& -- History; Spirituality -- Italy -- History; Women in Christianity -- Italy -- History; Women mystics -- Italy -- History; #GOSA:XX.III.C.Clar; 271-055.2 -- Vrouwelijke religieuze orden, congregaties; 396.7 -- Vrouw en religie; Italy -- Church history -- 15th century; Italy -- Church history -- 476-1400.